Match-Play Temporal and Position-Specific Physical and Physiological Demands of Senior Hurlers; Journal of Strength and Conditioning Research; Vol. 34, iss. 6 - Young D. Damien; Beato M. Marco; Mourot L. Laurent; Coratella G. Giuseppe (2020, 2020)
Title screen